Exposure of wheat to flameless catalytic infrared radiation on temperatures attained, wheat physical properties, microbial loads, milling yield, and flour quality - Deliephan, Aiswariya (Kansas State University, 2013)
Organic, hard red winter wheat of 11% moisture was tempered with distilled water to moisture levels of 16 and 18% and held for 8, 16, and 24 h. At each moisture and holding time wheat was unexposed (control) or exposed to infrared radiation for 1, 1.5, and 2 min using a bench-top flameless catalytic infrared emitter. The mean external grain temperatures for 16% mc wheat measured with thermocouples during infrared exposure of 1, 1.5, and 2 min ranged from 77.4-83.1, 93.7-101.2, and 91.2-98.3°C, respectively; corresponding mean internal temperatures were 67.3-76.4, 80.0-85.6, and 81.3-93.2°C. Minor differences in kernel moisture, hardness, and weight were observed among treatments. Tempered wheat after infrared exposure among treatments lost 1.5-2% moisture. Infrared exposure of wheat reduced initial bacterial loads (6.7×10[superscript]4 CFU/g) by 98.7% and fungal loads (4.3×10[superscript]3 CFU/g) by 97.8% when compared with those on untreated wheat. Wheat tempered to 18% and exposed for 2 min to infrared radiation lost 2% moisture, and this wheat when milled had a yield of 73.5%. The color of flour from infrared- exposed wheat was slightly dark (color change, ΔE = 0.31) when compared with untreated flour. Differential scanning calorimetry showed that flours from infrared exposed wheat had lower enthalpy (3.0 J/g) than those unexposed to infrared (3.3 J/g). These flours were adversely affected because they had longer mixing times (7-15 min) at all infrared exposures due to the presence of insoluble polymeric proteins (up to 60%). Microbial loads in flour from wheat tempered to 18% and exposed for 1-2 min had 0.6-2.4 log reduction compared to flour from untreated wheat. Wheat tempered to 18% moisture with electrolyzed-oxidizing (EO) water reduced bacterial and fungal loads up to 66%. EO water tempered wheat exposed for 1, 1.5, and 2 min to infrared radiation showed microbial reductions of 99.5% when compared with control wheat. Infrared treatment of tempered wheat cannot be recommended as it adversely affected flour functionality. The use of EO water for tempering as opposed to potable water that is generally used in mills slightly enhances microbial safety of hard red winter wheat.
Keywords: Infrared radiation; Electrolyzed oxidizing water; Wheat; Quality; Microbial loads; Food Science (0359); Microbiology (0410)